Creative negotiations - Romania-America 1920-1940 - ANDRAȘ, Sonia D.; MIHALY, Roxana (Presa Universitară Clujeană, 2024)
Throughout the interwar period, America’s interest in Romania grew and encompassed not only political, diplomatic, and historical aspects but also financial, cultural, and educational contributions. Thus, the Romanian- American ties throughout the interwar period suggest innate complexity and dynamism. This volume presents novel techniques and issues examined from an interdisciplinary, multi-perspective, and intercultural outlook. These approaches are derived from ideas such as discussion, negotiation, educational, and cultural communications.